Impact of natural control agents of the citrus leafminer Phyllocnistis citrella on lemon trees varies among seasons. Issue 6 (7th September 2015) - Goane, L.; Casmuz, A.; Salas, H.; Willink, E.; Mangeaud, A.; Valladares, G.
Abstract: Studies on insect natural enemies and their effects on host populations are of immense practical value in pest management. Predation and parasitism on a citrus pest, the leafminer Phyllocnistis citrella Stainton, were evaluated by sampling over 3 years in four locations within a world leading lemon producing area in Northwest Argentina. Both mortality factors showed seasonal trends consistent across locations, with predation exerting earlier and more sustained pressure than parasitism, which showed wider seasonal variations. The dominant parasitoids, native Cirrospilus neotropicus and introduced Ageniaspis citricola, showed different seasonal trends: C. neotropicus was dominant in spring whereas A. citricola superseded it in autumn and winter. Although parasitism rates were relatively low, the native C. neotropicus revealed favourable features as potential control agent, by showing density-dependence, parasitism rates comparable with those of the specific A. citricola during part of the cycle, and earlier synchronization with the host. The study provides highly relevant information for a sustainable management of this worldwide pest, for which biological control is considered the best long-term option.